2010
DOI: 10.1007/s12275-010-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori apo-Fur regulation appears unconserved across species

Abstract: The Ferric Uptake Regulator (Fur) is a transcriptional regulator that is conserved across a broad number of bacterial species and has been shown to regulate expression of iron uptake and storage genes. Additionally, Fur has been shown to be an important colonization factor of the gastric pathogen Helicobacter pylori. In H. pylori, Fur-dependent regulation appears to be unique in that Fur is able to act as a transcriptional repressor when bound to iron as well as in its iron free (apo) form. To date, apo-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…Moreover, the crystal structure of HpFur failed to provide structural insights into apo-HpFur function, and previous work has suggested that the structure of CjFur differed from other Fur-family proteins (33). Because our results indicate that CjFur recognizes divergent DNA consensus sequences and regulates gene expression independently of iron, we reasoned that CjFur must possess unique structural features that have not yet been described for the Fur family of proteins.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, the crystal structure of HpFur failed to provide structural insights into apo-HpFur function, and previous work has suggested that the structure of CjFur differed from other Fur-family proteins (33). Because our results indicate that CjFur recognizes divergent DNA consensus sequences and regulates gene expression independently of iron, we reasoned that CjFur must possess unique structural features that have not yet been described for the Fur family of proteins.…”
Section: Discussionmentioning
confidence: 70%
“…In this sense, Fur participates in gene activation and iron-independent regulation of a variety of genes involved in distinct functions (6,36).…”
Section: Innovationmentioning
confidence: 99%
“…2B). apo-Fur repression has been primarily characterized in H. pylori and has not yet been well described in other bacteria (13,72). Although iron may not be important for apo-Fur function, it is possible that other metal ions play a role in apo-Fur-mediated transcriptional control (24,74,91).…”
Section: Fur Functions As a Global Regulatory Proteinmentioning
confidence: 99%
“…Similar to N. meningitidis, gonococcal Furrepressed genes include a large number involved in iron acquisition (Table 2). However, only three genes or loci encoding proteins for energy metabolism and biosynthesis (fumC, NGO0108, and NGO0114) are identified as being Fur repressed in N. gonor- (13,72). (C) In the apo-Fur activation mechanism, Fur does not bind to the promoter region; thus, gene transcription is not active when iron is present (left panel).…”
Section: Fur Regulon Of N Gonorrhoeaementioning
confidence: 99%